Effect of Sample Preparation and Extended Mix Times with Different Salt Particle Sizes on the Uniformity of Mix of a Corn-Soybean Meal Swine Diet - M. Saensukjaroenphon; C. K. Jones; C. H. Fahrenholz; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2016)
The uniformity of a feed mixture is determined from the coefficient of variation (CV) of 10 samples in a single batch of feed. The feed industry standard is a CV of less than 10% using a single source tracer, such as salt, trace minerals, or iron filings. The objectives of these experiments were to determine the effects of 1) extended mix time, 2) particle size of the marker, and 3) sample preparation on the CV in a corn-soybean meal swine diet. In Experiment 1, treatments were arranged in a 3 × 7 factorial with main effects of 3 salt particle sizes (fine-350μm, medium-464μm, and coarse-728μm) and 7 mix times (2, 3, 5, 15, 30, 45, and 60 min). In Experiment 2, treatments were arranged in 2 × 3 × 3 factorial with 2 sample preparations (unground vs. ground), 3 salt particle sizes (fine-350μm, medium-464μm, and coarse-728μm) and 3 mix times (3, 30, and 60 min). There were 3 replicates per treatment and 10 samples per replicate. Salt concentrations were determined using a Quantab®Chloride Titrator. The result of Experiment 1 indicated no interaction between mix time and salt particle size. The extended mix time did not result in segregation (P = 0.307). Particle size of the salt significantly affected the uniformity of mix (P<0.0001; 21.2, 8.6, and 7.9% CV for the coarse, medium, and fine salt, respectively). The results of Experiment 2 indicated no interaction of sample preparation, salt particle size, and mix time. However, there was interaction between sample preparation and salt particle size (P = 0.0002). The difference in the CV% between unground and ground samples was significantly greater for the mixture with coarse salt (8.89 %) than the mixture with fine (1.35 %) and medium salt (2.59 %). The ground treatment had a significantly lower CV than the unground treatment (P<0.0001; 8.7 and 13.0 for ground and unground samples, respectively). The fine and medium salt treatments had significantly lower CV as compared to the coarse salt treatment. (P<0.0001; 7.4, 7.7, and 17.4 for fine, medium and coarse, respectively). These results indicated that feed did not segregate after mixing for up to 1 h. The greater number of particles per gram of the marker (in this case salt) increased the precision of the analysis, likely due to an increased probability that the marker was present in proportionate quantities in the sample tested. However, when coarse salt is used in the manufacturing process, the samples should be ground prior to analysis.
Keywords: mix time; particle size; sample preparation; uniformity of mix